Early Enrichment and Restitution of the Peripheral Blood Treg Pool Is Associated With Rejection-Free Stable Immunosuppression After Liver Transplantation. Issue 7 (July 2016) - Haarer, Jan; Riquelme, Paloma; Hoffmann, Petra; Schnitzbauer, Andreas; Schlitt, Hans J.; Sawitzki, Birgit; Geissler, Edward K.; Hutchinson, James A.
Abstract : Supplemental digital content is available in the text.